Central Bank Capital as an Instrument of Monetary Policy - Mojmir Hampl; Tomas Havranek (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2018)
We examine the use of central bank capital as an unconventional monetary policy tool. In this setting, a central bank employs digital currency to transfer digital cash to each household, thus supporting consumption directly when needed. The asset side of the central bank's balance sheet remains unchanged, and the creation of new digital cash is offset by a decrease in central bank capital. The central bank thus incurs an immediate loss but does not take on any additional risks for its future income statements. We address several objections to this policy, paying particular attention to the claim that weakening the financial strength of the central bank endangers long-term price stability. Through a meta-analysis of 176 estimates reported previously in the literature, we find that central bank financial strength has not historically correlated with inflation performance.
Keywords: E42; E52; E58; 330; Central bank capital; inflation; seigniorage; monetary policy; helicopter money; central bank digital currency